PROGRAM EMPLOYEE RELATIONS DALAM MEMOTIVASI KARYAWAN PADA PINGU’S ENGLISH SCHOOL PEKANBARU - Anisah Septia Maheldi; Tantri Puspita Yazid (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Employees is one part of the internal public company that is a key element in achieving the goal. During this time many companies that focus on the relationship with outsiders, but ignore the relationship with its employees. Employee relations is a form of cooperation between all parties in the company. If the employee relations goes well, then the enthusiasm and motivation will increase. One company that realizes the importance of this is Pingu's English School Pekanbaru. Some of the activities undertaken to establish a good relationship is another gymnastics on Wednesday morning, lunch on Friday, as well as a cinema if the films box office. This study bertujan to find out more about employee relations program that run Pingus English School in motivating employees.This research uses descriptive qualitative method. The results of the research associated with the theory of S-O-R (Stimulus-Organism-reponse). Stimulus in penelilitian is a program of employee relations, acceptance by employees, then cause a response in the form of motivation. As for the informant is the Board Of Directors, Public Relations, Customer Cervice Coord, Customer Cervice, Teacher Coordinator, Full-time teacher and Operational Coord. Data collected by interview. The results of the interview, then analyzed using a model of interactive data analysis Miles and Huberman. The results of the analysis of its validity is checked using the technique of extension of participation, which confirms the parties are considered competent, as well as with triangulation techniques, comparing observations with interviews.The results showed that Pingu's English School run fourth employee relations program. Employee communication program in the form of appraisal activities, regular meetings, training, cultural openness, and special activities to establish kinship. Appraisal or award programs into activities that are most motivating to employees. Program employee attitude surveys carried out by the performance assessment activities formally and informally. Both are equally build motivation, because employees feel watched so always act according to the standard of performance. Employee counseling program consists of consultancy service activities, brainstorming, coaching, and visit sick employees. Coaching be the most motivating activity, because employees feel the company gives attention to improving the skills and Performance. Profit sharing consists of salary, bonus, vacation, recreation and career. It is very motivating is wages and bonuses, for the purpose of working is earning